Effects of vibrotactile feedback on postural sway in trans-femoral amputees: A wavelet analysis - Khajuria, Aayushi; Joshi, Deepak (Journal of biomechanics, 2021)
Loss of somatosensory feedback after amputation inflicts a serious challenge to achieve postural stability. Improving motor skills by incorporating sensory feedback in rehabilitation protocols for persons with lower limb amputation has been gaining traction over time. However, the control mechanisms involved in this regarding time–frequency analysis have not been investigated yet. The purpose of this study was to explore the frequencies/time-scales responsible for postural stability in trans-femoral amputees with vibrotactile feedback. Center of Pressure (COP) signals were collected from 5 trans-femoral amputees and 10 healthy subjects during weight shifting balance tasks. A customized foot insole was used to estimate the COP for actuation of vibratory feedback. The evaluation of postural sway fluctuations by means of COP excursions with vibrotactile feedback was computed by wavelet transform method. Vibrotactile feedback was found to be effective in controlling low frequency postural sway in amputees. We found significantly higher energy (p = 0.004, 0.0007) at shorter time-scales (j = 6,7, freq. = 0.6–1.25 Hz) and lower energy (p = 0.0006) at longer time-scale (j = 10, freq. = 0.078 Hz) in amputees with vibrotactile feedback in comparison to healthy subjects using Coif 1 wavelet. We also found significant increase in energy (p = 0.003) during forward weight shifting with vibrotactile feedback in the sound limb of amputees in comparison to no feedback session at frequency/time-scales corresponding to somatosensory acuity (j = 6–8, freq. = 0.3–1.5 Hz) using Haar wavelet. These findings reflect the higher contribution of somatosensory receptors in amputees with vibrotactile feedback and may provide a better understanding of the mechanisms associated with standing balance in terms of time–frequency analysis.